2001
DOI: 10.1126/science.1058574
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Productivity Collapse Associated with the Triassic-Jurassic Boundary Mass Extinction

Abstract: The end-Triassic mass extinction is one of the five most catastrophic in Phanerozoic Earth history. Here we report carbon isotope evidence of a pronounced productivity collapse at the boundary, coincident with a sudden extinction among marine plankton, from stratigraphic sections on the Queen Charlotte Islands, British Columbia, Canada. This signal is similar to (though smaller than) the carbon isotope excursions associated with the Permian-Triassic and Cretaceous-Tertiary events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
154
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 7 publications
3
154
0
1
Order By: Relevance
“…Dramatic reductions in primary production are thought to have characterized major mass extinction episodes in the past (22) and episodes of climate change, such as the more recent interglacials (41). During the end-Cretaceous extinction event, changes in ocean nutrient supply may have been a crucial factor in driving echinoid extinction because of the preferential survival of depositfeeding taxa such as spatangoids (42).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dramatic reductions in primary production are thought to have characterized major mass extinction episodes in the past (22) and episodes of climate change, such as the more recent interglacials (41). During the end-Cretaceous extinction event, changes in ocean nutrient supply may have been a crucial factor in driving echinoid extinction because of the preferential survival of depositfeeding taxa such as spatangoids (42).…”
Section: Resultsmentioning
confidence: 99%
“…At intervals throughout evolutionary history, organisms have faced large-scale collapses of primary productivity due to abiotic environmental changes, such as volcanism and global warming, that often are associated with mass extinctions of species (22,23). This raises the possibility that random search patterns such as Lévy walks, with characteristic long steps to new locations, might have acted to increase the likelihood of ancient organisms finding scarce resources, as the search time to find distant patches is minimized in this movement strategy compared with Brownian motion (2).…”
mentioning
confidence: 99%
“…1-3) suggests that per-plate extinction risk varied considerably among genera. Each of these events also is associated with geological and geochemical evidence for rapid, global environmental disruption coincident with geologically rapid extinction (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Previous studies have identified ecological and physiological extinction selectivity patterns that may account for differences in per-plate extinction risk among genera during these intervals.…”
Section: Discussionmentioning
confidence: 99%
“…[The longer period of 13 C-depleted values during the CAMP extrusion might be the result of the biotic crisis itself (9).] A carbon dioxide super-greenhouse is supported by paleobotanical studies (10) and evidence of a crisis among calcareous organisms in the oceans (11).…”
Section: Causes Of Extinctionmentioning
confidence: 73%